Keterampilan Bahasa Produktif Sebagai Pilar Utama Literasi Komunikasi - Perangin-angin, Great Novie; Azizah, Nurul; Azzahra, Naila; Aritonang, Carnila; Sipahutar, Rio; Siahaan, Thesaloni Octapia (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Productive language skills, which include speaking and writing, are vital components of communication literacy. This study aims to explore the role of productive language skills as a key pillar in the context of communication in general. Through descriptive qualitative methods with literature review, this research finds that speaking skills enable individuals to express ideas and feelings clearly, as well as enhance confidence in social interactions. Meanwhile, writing skills contribute to the organization of thoughts and systematic information delivery, which is crucial in the professional world. This study is expected to provide deeper insights into the importance of productive language skills in enhancing communication effectiveness across various aspects of life.